تمظهرات التاريخ الإسلامي في الرواية الجزائرية "رواية الولي الطاهر يعود إلى مقامه الزكي" أنموذجا - سلام, حسينة (University of Eloued جامعة الوادي, 2017)
تتناول هذه المقالة واحدة من إبداعات الطاهر وطار" الولي الطاهر يعود الى مقامه الزكي" التي يسعى من خلالها إلى إعادة قراءة التاريخ الإسلامي والتّأكيد على مقولة أنّ التاريخ يعيد نفسه, من خلال تركيزه على تيمة القتل باسم الدين التي نعيشها في عصرنا الحالي, حيث يتقاطع الواقعي والتخيلي وفق لغة سردية تناصية مع التراث الديني والتاريخي كاشفة عن رؤية رفضية واحتجاجية لما كان وما هو كائن ومتخوفا مما سيكون.هذه الرواية والتي تحمل بين طياتها الكثير من التجريد السريالية تتصارع فيها أفكار سياسية وثقافية واجتماعيه يدور رحاها في الماضي والحاضر تصوّر الأحداث التاريخية تصويرا فنيا وملحميا بتعبير صوفي ورؤية سياسية. تجعل من الحوار والمونولوج والاستحضار التناصي للشخصيات الدينة الإسلامية مرتكزا تعاين من خلاله الواقع الروائي الممثّل, تمثيلا حقائقيا أو تخيليا , ينطلق من رؤية الروائي الخاصة للعالم والواقع والتاريخ الإسلامي في حدّ ذاته.الأمر الذي يدعو إلى جملة من التساؤلات نتوخى مقاربتها في هذه الأسطر.من أهمها: كيف تمثّل التاريخ الإسلامي في الرواية؟ وهل استطاع الروائي أن يُقنع المتلقي بأفكاره النقدية؟ وهل كانت عودته إلى مقامه الزكي عودة موفقة أم مستحيلة؟ وهل العودة إلى التّاريخ الإسلامي عودة لها مبرراتها في الرواية؟ وعليه سنحاول استجلاء أهم المحطات المتعلقة بالتاريخ الإسلامي في الرواية وتحليلها للكشف عن وعي السارد ومدى إدراكه لوضعه وحساسيته سواء الدينية أو السياسية Manifestations of Islam history in contemporary Algerian novel “wail Tahar back to his place innocent*- model *- This article deals with one of the creations of Al-Tahir and Tariq al-Wali al-Tahir, which is based on his zakih position, in which he seeks to re-read Islamic history and to emphasize that history repeats itself by focusing on the theme of murder in the name of the religion we live in today, Realistic and imaginative according to the language of narrative contradictions with the religious and historical heritage revealing a vision of rejection and protest of what was and what is and is afraid of what will be. This novel, which carries a lot of abstraction and surrealism, struggling with political, cultural and social ideas, revolves in the past and present, And a political vision. It makes the dialogue, monologue and the evolution of the Islamic religious figures a basis in which the reality of the narrator is represented, a representation of fact and fiction, based on the vision of the novelist of the world and the reality and Islamic history in itself. This raises a number of questions. The most important of these are: How does Islamic history represent the novel? Was the novelist able to convince the recipient of his critical ideas? Was his return to his place Zaki a successful or impossible return? Is the return to Islamic history a return to its justification in the novel? From here we will try to clarify the most important stations related to Islamic history in the novel and analyze it to reveal the awareness of the narrator and his awareness of his status and sensitivity, whether religious or political.
Keywords: الطاهر وطار، الولي الطاهر يعود الى مقامه الزكي، التاريخ الإسلامي; Tahar Ouettar, Al-Tahir and Tariq al-Wali al-Tahir, Islamic history